(untitled) (Global Journal of Management and Business Research, 2014)
The purpose of this study is to investigate affects of country of origin on branded clothing by female consumers. As expected, regression analysis clearly illustrates the topical relevance of the issue and country of origin has found significant impact on female consumer’s perception of choosing branded clothing. Factor analysis has been performed to identify most preferred factors that led by 26 key factors. This result will help marketer to set strategy by understanding market insights and it might be useful to academicians, manufacturers and other applied researchers now and in the future. This paper could help marketing managers employ promotional techniques that deemphasize, downplay or avoid the COO information in order to prevent or reduce any risks if a country’s image is unfavorable. Conversely, firms may choose to emphasize COO if the country’s image is favorable.